IDENTIFICATION OF PLACEMAKING POTENTIALITY ON THEMATIC PARK IN BANDUNG CITY - Ramadhani, Bungaria
City park is an important element in a city to reach environmental balance. As the time goes by, park development is getting more diverse, from the garden which formed as a natural space for relaxation and it’s very far away from urban areas, to the formation of park in a city that is more recreational, and then change again towards the park which is more concerned with the environment. At this time, there is an emerging new concept that called creative placemaking where the park is formed by applying a characteristic that make up the character of a space. Bandung since the end of 2013 made a new breakthrough on the public space development. Parks in Bandung got reshaped by applying certain characteristics, or better known as “thematic park”s. Thematic parks that already exists is not yet known whether actually characterize the local character to be able to create a livable and sustainable park or not. So the identification of the potential formation of a creative public space needs to be done as a foundation for improving the quality and quantity of Bandung’s public places. After analyzing the data with qualitative descriptive analysis, the findings obtained about thematic park initiator, the suitability of design and functionality, and stakeholder involvement. Thematic park initiator in Bandung in general is mostly done by the government, especially the mayor. The suitability of the design and functions between the characteristic and usage is quite ideal even still there are weaknesses on some components. Theme-based activity was served in the park in order to maximize all the facilities. The biggest stakeholder responsibility for thematic parks is held mostly by the government, then the community and the private sector. Based on the analysis, it can be concluded that there is a potentiality of making creative public space in Bandung.